Emprego da RMN aliada à quimiometria no controle de qualidade de suco de laranja - Oliveira, Clayton Rodrigues de (Universidade Federal de São Carlos, 2012)
Fresh orange juice is widely appreciated all over the world for its pleasant flavor and because it is a great source of nutrients. Currently, Brazil leads the world in the production and export of orange juice, generating billions of dollars each year. Therefore, the purpose of this paper is to describe the application of 1H NMR in combination with chemometrics in order to characterize the chemical properties of commercial juices and to compare them with natural juices from the main types of Citrus sinensis cultivated in Brazil and bought in the local market. Moreover, the degree of alteration and the variation in concentrations of derived chemical constituents of commercial and natural juices in different storage conditions were evaluated. Hence, three (3) samples of commercial juices and five (5) types of natural juices extracted from pêra Rio oranges (C. sinensis (L.) Osbeck), Bahia oranges (C. sinensis (L.) Osbeck), murcote oranges (C. grandis (L.) Osbeck), lima oranges (C. aurantifolia), and lima da Pérsia oranges (C. aurantifolia) were studied. The 2D and 1H NMR techniques had proved to be an important tool for characterization and relative quantification of the main metabolites that are found in the alteration of natural and commercial orange juice samples of this study. The application of these techniques has allowed the characterization of twenty seven (27) metabolites present in orange juice samples examined herein. The results showed that the absolute quantification of ethanol and the relative quantification for formic, fumaric, lactic, acetic, pyruvic, and succinic acids indicate that these compounds changes in the orange juice occurred during the storage period and conditions. Furthermore, principal components analysis (PCA) was used to classify commercial and natural orange juice through quantification of major and minor metabolites present in juices.
Quality control in orange juice using nmr and chemometrics
Keywords: Química quantitativa; Ressonância magnética nuclear; Quimiometria; Suco de laranja; CIENCIAS EXATAS E DA TERRA::QUIMICA